Disseminating Cardiopulmonary Resuscitation Training by Distributing 9, 200 Personal Manikins. (24th August 2014) - de Paiva, Edison Ferreira; de Queiroz Padilha, Roberto; Sgobero, Jenny Karol Gomes Sato; Ganem, Fernando; Cardoso, Luiz Francisco; O'Neil, Brian
Abstract Objectives Community members should be trained so that witnesses of cardiac arrests are able to trigger the emergency system and perform adequate resuscitation. In this study, the authors evaluated the results of cardiopulmonary resuscitation (CPR) training of communities in four Brazilian cities, using personal resuscitation manikins. Methods In total, 9, 200 manikins were distributed in Apucarana, Itanhaém, Maringá, and São Carlos, which are cities where the populations range from 80, 000 to 325, 000 inhabitants. Elementary and secondary school teachers were trained on how to identify a cardiac arrest, trigger the emergency system, and perform chest compressions. The teachers were to transfer the training to their students, who would then train their families and friends. Results In total, 49, 131 individuals were trained (6.7% of the population), but the original strategy of using teachers and students as multipliers was responsible for only 27.9% of the training. A total of 508 teachers were trained, and only 88 (17.3%) transferred the training to the students. Furthermore, the students have trained only 45 individuals of the population. In Maringá and São Carlos, the strategy was changed and professionals in the primary health care system were prepared and used as multipliers. This strategy proved extremely effective, especially in Maringá, where 39, 041 individuals were trained (79.5% of the total number of trainings). Community health care providers were more effective in passing the training to students than the teachers (odds ratio [OR] = 7.12; 95% confidence interval [CI] = 4.74 to 10.69; p < 0.0001). Conclusions Instruction of CPR using personal manikins by professionals in the primary health care system seems to be a more efficient strategy for training the community than creating a training network in the schools.